SURXONDARYO VILOYATI SABZAVOT EKINLARIDAGI ILDIZ PARAZIT NEMATODALAR - Eshnazarov K, Eshnazarov K; Sherimmetova G. H., Sherimmetova G. H.; Maxmudov A. Y., Maxmudov A. Y. (Actual problems and prospects of the study of the fauna, 2024)
The article describes the study of root parasites nematodes belonging to the Hoplalaimidae family, their morphological characteristics, especially the structure of their bodies, and the types found in vegetable crops in the Surkhandarya region.